2004
DOI: 10.1111/j.0965-075x.2004.00273.x
|View full text |Cite
|
Sign up to set email alerts
|

Fairness Reactions to Personnel Selection Techniques in Spain and Portugal

Abstract: This paper examines the reactions to personnel selection methods in Spain and Portugal using a sample composed of 125 and 104 students, respectively. The results found are very similar in both countries. The best rated and most favorable methods are interviews, résumés and work sample tests, while contacts, integrity tests and graphology were the least favorable ones. With regard to the process dimensions used, face validity and opportunity to perform are the most important bases for considering personnel tech… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
97
5

Year Published

2008
2008
2022
2022

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(109 citation statements)
references
References 28 publications
7
97
5
Order By: Relevance
“…The difference between the reactions to the two personnel selection methods was large -about one standard deviation. This pattern is consistent with the literature that reported that selection interviews are perceived as more fair and gain more favorable reactions from applicants relative to previous grades or cognitive test scores (Marcus, 2003;Moscoso & Salgado, 2004;Smither et al, 1993;Steiner & Gilliland, 1996).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The difference between the reactions to the two personnel selection methods was large -about one standard deviation. This pattern is consistent with the literature that reported that selection interviews are perceived as more fair and gain more favorable reactions from applicants relative to previous grades or cognitive test scores (Marcus, 2003;Moscoso & Salgado, 2004;Smither et al, 1993;Steiner & Gilliland, 1996).…”
Section: Discussionsupporting
confidence: 91%
“…Recruiting organizations recognize the importance of applicants' reactions to selection methods for reasons such as their ability to attract applicants and validity considerations (Rynes, 1993;Schmitt, Oswald, Kim, Gillespie, & Ramsay, 2004;Smither, Reilly, Millsap, Pearlman, & Stoffey, 1993). Research regarding applicants' reactions to personnel selection methods (also labeled techniques or procedures) examined correlates of applicants' individual differences (Wiesenfeld, Swann, Brockner, & Bartel, 2007) and compared reactions to different selection methods in an American sample (Smither et al, 1993) or international samples (Anderson & Witvliet, 2008;Marcus, 2003;Moscoso & Salgado, 2004;Phillips & Gully, 2002;Steiner & Gilliland, 1996).…”
Section: Introductionmentioning
confidence: 99%
“…To our knowledge, Moscoso and Salgado (2004) were the first authors to argue that reactions would vary as a function of countryspecific variables, such as employment legislation, human resource management practices, culture, and socioeconomic status; they posited that "cross-cultural differences may moderate . .…”
Section: Research Trend 3: Sustained and Increased Focus On Internatimentioning
confidence: 99%
“…For instance, in France the wide use of graphology increased its perceived fairness, so it is seen as face valid despite its low predictive validity. However, it is rated low with American (Steiner & Gilliland, 1996), Portuguese, and Spanish subjects (Moscoso & Salgado, 2004).…”
Section: Fairness Perceptions Of Selection Instruments and Goal Orienmentioning
confidence: 94%